The Sacrifice of a Husband Reflected in "Oscar Wilde's an Ideal Husband Drama: Psychoanalytic Approach" - Anggraini, Selvian; , Dr. Phil. Dewi Candraningrum, M.Ed; , Mauly Halwat Hikmat, Ph. D (2015)
The major problem ofthis study is how anxiety arises in major character's personality. Then the other problem is how she tries to overcome it. the aimof thestudy is to analyze Oscar Wilde An Ideal Husband based on the structural elements of the drama and personality of the major character, namely Sir Robert Chiltren. The benefits of the study areto give some contribution to the development oflarger body of knowledge about literary work. The study uses library data; the primary data are taken from the novel itself, while the secondary data are taken fromsome information needed. The methode of data collection is descriptive qualitative research. the study employs Sigmund Freud's Psychoanalysis to answer the problem. The result of this study show that the problem of the major character causes the conflict of her mental condition. Then, it develops to be anxiety that makes her does some defenses to overcome her anxiety